Collaboration, Not Calculation: A Qualitative Study of How Hospital Executives Value Hospital Medicine Groups. Issue 11 (24th July 2019) - White, Andrew A; McIlraith, Thomas; Chivu, Anton M; Cyrus, Rachel; Cockerham, Christopher; Vora, Hardik; Vulgamore, Patrick
Abstract : BACKGROUND: Hospital medicine groups (HMGs) typically receive financial support from hospitals. Determining a fair amount of financial support requires negotiation between HMG and hospital leaders. As the hospital medicine care model evolves, hospital leaders may regularly challenge HMGs to demonstrate the financial value of activities that do not directly generate revenue. OBJECTIVE: To describe current attitudes and beliefs of hospital executives regarding the value of contributions made by HMGs. DESIGN: Thematic content analysis of key informant interviews. PARTICIPANTS: Twenty‐four healthcare institutional leaders, including hospital presidents, chief medical officers, chief executive officers, and chief financial officers. Participants comprised a diverse sample from all regions in the United States, including rural, suburban, and urban locations, and academic and nonacademic institutions. RESULTS: Executives highly valued hospitalist groups that demonstrate alignment with hospital priorities, and often used this concept to summarize the HMG's success across several value domains. Most executives evaluated only a few key HMG metrics, but almost no executives reported calculating the HMG return on investment by summing pertinent quantitative contributions. Respondents described an evolving concept of hospitalist value and believed that HMGs generate substantial value that is difficult to measure financially. CONCLUSIONS: Hospital executives appear to make financial support decisions based on a small number of basic financial or care quality metrics combined with a subjective assessment of the HMG's broader alignment with hospital priorities. HMG leaders should focus on building relationships that facilitate dialog about alignment with hospital needs.